2019
DOI: 10.1016/j.resuscitation.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial airway strategy on time to epinephrine administration in patients with out-of-hospital cardiac arrest

Abstract: Introduction: Epinephrine and advanced airway management are commonly used during treatment of out-of-hospital cardiac arrest (OHCA). Recent studies suggest that early but not late administration of epinephrine is associated with improved survival. The purpose of this study was to evaluate the effect of initial airway strategy on timing to the first epinephrine dose in OHCA. Methods: This is a secondary analysis of patients enrolled in the Pragmatic Airway Resuscitation Trial who had an advanced airway attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Izawa et al [ 9 ] demonstrated that in their early AAM group, their patients also received early epinephrine administration. In contrast, Lupton et al [ 13 ] did not find an association between AAM and time to initial epinephrine administration in out-of-hospital cardiac arrest. This finding might be explained by the effect of high performance of the CPR team; with more effective resuscitation, epinephrine can be administered immediately, and the advanced airway can be also placed early.…”
Section: Discussionmentioning
confidence: 91%
“…Izawa et al [ 9 ] demonstrated that in their early AAM group, their patients also received early epinephrine administration. In contrast, Lupton et al [ 13 ] did not find an association between AAM and time to initial epinephrine administration in out-of-hospital cardiac arrest. This finding might be explained by the effect of high performance of the CPR team; with more effective resuscitation, epinephrine can be administered immediately, and the advanced airway can be also placed early.…”
Section: Discussionmentioning
confidence: 91%
“…For adult patients in cardiac arrest, epinephrine administration in the early stage and after the third shock is recommended for non-shockable and shockable rhythms, respectively 4 . Another study showed that administering epinephrine within 10 min after scene arrival was associated with improved survival among patients with OHCA 5 . However, the required intravenous access and other advanced interventions may negatively impact the quality of chest compressions 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For adult patients in cardiac arrest, adrenaline administration in the early stage and after the third shock is recommended for non-shockable and shockable rhythms, respectively [4]. Another study showed that administering adrenaline within 10 min after scene arrival was associated with improved survival among patients with in OHCA [5]. However, the required intravenous access and other advanced interventions may negatively impact the quality of chest compressions [6].…”
Section: Introductionmentioning
confidence: 99%